MODERASI ISLAM INDONESIA DALAM MEDIA CETAK - Dudung Abdul Rohman (Tatar Pasundan : Jurnal Diklat Keagamaan, 2020)
This research departs from the phenomenon of widespread acts of violence with religious nuances that often occur in Indonesia. A negative stigma is often addressed to the Muslim community. In this context, moderation narrative of Indonesian Islam published by the Ministry of Religion through the printed media Republika Newspaper is essential to reduce and counteract the issues of radicalism and religious terrorism. The results indicate that the media takes a role in constructing narrative news about the moderation conception of Indonesian Islam from the perspective of the Ministry of Religion, so that it becomes a presentation of information and public opinion. After being analyzed, the moderation conception of Indonesian Islam includes: (1) Islam rahmatan lil-alamin; (2) Islam that promotes openness, brotherhood, and benefit; (3) Islam which is based on tolerance, justice, and balance; (4) Islam which is comprehensively understood; (5) Islam which is not radical or extreme. Keywords: Discourse Analysis; Print media; Narrative of Islamic Moderation.